2007
DOI: 10.1002/hipo.20256
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation with a simple exposure to the experimental environment is sufficient to induce reconsolidation requiring protein synthesis in the hippocampal CA3 region in mice

Abstract: Our understanding of the memory reconsolidation process is at an earlier stage than that of consolidation. For example, it is unclear if, as for memory consolidation, reconsolidation of a memory trace necessitates protein synthesis. In fact, conflicting results appear in the literature and this discrepancy may be due to differences in the experimental reactivation procedure. Here, we addressed the question of whether protein synthesis in the CA3 hippocampal region is crucial in memory consolidation and reconso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
4
25
0
Order By: Relevance
“…These findings are consistent with those of many prior studies involving injections of protein synthesis inhibitors into the hippocampus (e.g., Bourtchouladze et al 1998;Quevedo et al 1999Quevedo et al , 2004Taubenfeld et al 2001;Barriantos et al 2002;Agnihotri et al 2004;Artinian et al 2007), as well as into other brain areas such as the amygdala (Nader et al 2000;Schafe and LeDoux 2000;Debiec et al 2002;Duvarci et al 2005;Parsons et al 2006;Milekic et al 2007), and prefrontal cortex (Santini et al 2004;Akirav and Maroun 2006;Touzani et al 2007). These reports are part of a large set of papers showing that direct brain injections of protein synthesis inhibitors produce amnesia for many tasks (cf.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of many prior studies involving injections of protein synthesis inhibitors into the hippocampus (e.g., Bourtchouladze et al 1998;Quevedo et al 1999Quevedo et al , 2004Taubenfeld et al 2001;Barriantos et al 2002;Agnihotri et al 2004;Artinian et al 2007), as well as into other brain areas such as the amygdala (Nader et al 2000;Schafe and LeDoux 2000;Debiec et al 2002;Duvarci et al 2005;Parsons et al 2006;Milekic et al 2007), and prefrontal cortex (Santini et al 2004;Akirav and Maroun 2006;Touzani et al 2007). These reports are part of a large set of papers showing that direct brain injections of protein synthesis inhibitors produce amnesia for many tasks (cf.…”
Section: Discussionsupporting
confidence: 92%
“…Morris et al (2006) showed that inactivation of the dorsal hippocampus during reconsolidation by anisomycin (a protein synthesis inhibitor) has no effect on the MWM performances. However, in previous studies (Artinian et al 2007(Artinian et al , 2008, we showed that the hippocampal CA3 region is crucial for reconsolidation of spatial information in this same task. Different factors could explain this apparent discrepancy, but the most important fact is that, unlike us, Morris et al (2006) used a distributed learning procedure leading to an asymptotic level of performances before the reactivation trial.…”
mentioning
confidence: 61%
“…They were tested during the first half of the light period. The strain of mice was chosen for their very good performances in spatial memory (Artinian et al 2007(Artinian et al , 2008. Moreover, CD1 mice exhibit a high endurance that is necessary in a massed procedure in the MWM.…”
Section: Experimental Subjectsmentioning
confidence: 99%
See 2 more Smart Citations